Leveraging Local Wisdom in Curriculum Design to Promote Sustainable Development in Rural Schools - Wahyuni, Erna; Tandon, Meredith; Jonathan, Bouyea (Journal of Social Science Utilizing Technology, 2024)
Background. Rural schools often face challenges in promoting sustainable development due to limited resources and the disconnect between global educational frameworks and local contexts. Local wisdom, rooted in the cultural and environmental knowledge of rural communities, offers valuable insights that can be integrated into curriculum design to foster sustainability and relevance in education. Despite its potential, the integration of local wisdom into formal education remains underutilized in many rural areas, limiting the impact of education on sustainable development. Purpose. This study aims to explore how local wisdom can be leveraged in curriculum design to promote sustainable development in rural schools. Method. Using a qualitative case study approach, the research involved interviews and focus group discussions with educators, community leaders, and students from three rural schools. The study examined existing curricula, identified elements of local wisdom, and explored ways to incorporate these elements into formal education. Data were analyzed thematically to identify key strategies for integrating local wisdom into teaching practices. Results. The findings reveal that incorporating local wisdom into the curriculum enhances students’ understanding of sustainable practices by connecting global sustainability goals with local knowledge and practices. Educators and community leaders played a critical role in bridging this gap, creating a more relevant and contextually grounded learning experience for students. The study also highlights the importance of collaboration between schools and local communities in fostering a sense of ownership and responsibility for sustainable development. Conclusion. In conclusion, leveraging local wisdom in curriculum design can significantly contribute to sustainable development in rural schools by creating more relevant, practical, and community-centered learning experiences. Further research is recommended to explore scalable models for integrating local knowledge into educational frameworks.